One-year clinical outcomes following Edwards INSPIRIS RESILIA aortic valve implantation in 487 young patients with severe aortic stenosis: a single-center experience - Porto, Alizee; Stolpe, Gregoire; Badaoui, Rita; Boudouresques, Vincent; Deutsch, Cornelia; Amanatiou, Cecile; Riberi, Alberto; Gariboldi, Vlad; Collart, Frédéric; Theron, Alexis (Frontiers in Cardiovascular Medicine, 2023)
The use of an aortic bioprosthesis is on the rise in younger patients with severe aortic stenosis despite the risk of accelerated structural valve degeneration (SVD). In the search for an optimal valve substitute that would not be prone to SVD, the INSPIRIS bioprosthesis represents a promising solution to lowering the risk of SVD. Here, we report the 1-year outcomes of the INSPIRIS-RESILIA aortic bioprosthesis in a population of young patients who underwent aortic valve replacement. In this prospective single-center study, we included all consecutive patients receiving INSPIRIS-RESILIA bioprosthesis between June 2017 and July 2021. Patients with isolated severe aortic regurgitation were excluded. Clinical assessment and transthoracic echocardiography were performed preoperatively and at 1 year post-operatively. The primary outcome was overall mortality at one year. A total of 487 patients were included. The mean age was 58.2 ± 11.5 years, 75.2% were men. Most of the interventions were elective, with a mean EuroSCORE II of 4.8 ± 7.9. The valve annulus size in most cases was either 23mm or 25mm. Overall mortality at 1-year was 4.1%. At 1-year, 7 patients (1.4%) had a stroke, 4 patients (0.8%) had a myocardial infarction, and 20 patients (4.1%) were hospitalized for congestive heart failure. The Kaplan-Meier estimated survival rates and survival without major adverse cardiac events at 1-year were 96.4% and 96.7 %, respectively. At 1-year follow-up, 10 patients (2.1%) had endocarditis and 1 patient (0.2%) had partial prosthetic thrombosis. Pacemaker implantation at 1-year post-operative was necessary in 27 patients (5.5%). Severe patient prosthesis mismatch and severe intra valvular regurgitation were 1.2% and 0.6%, respectively. The Kaplan-Meier estimated survival rates at 1-year of no infective endocarditis preoperative and infective endocarditis preoperative were 97.9 ± 0.7 % and 89.5 ± 3.3 %, respectively (p<0.001). Excluding endocarditis-related complication, no structural valve deterioration and no valve failure requiring redo surgery were reported. This is the largest single-center descriptive study of the 1-year outcomes after INSPIRIS RESILIA bioprosthesis implantation. The EDWARDS INSPIRIS RESILIA bioprosthesis provides encouraging clinical outcomes with an excellent 1- year survival rates and good hemodynamic performance. Long-term studies are mandatory to assess valve durability.